The impact of sarcopenia on the efficacy of PD-1 inhibitors in non-small cell lung cancer and potential strategies to overcome resistance - Zhenchao Liu; Tianxiang Lei; Yunliang Guo; Chongwen Zheng (Frontiers Media S.A., 2024)
Recent studies have revealed that sarcopenia can adversely affect the efficacy of PD-1 inhibitors in the treatment of non-small cell lung cancer (NSCLC). PD-1 inhibitors are immune checkpoint inhibitors widely used in the treatment of various cancers. However, NSCLC patients may have poorer outcomes when receiving PD-1 inhibitor treatment, and sarcopenia may affect the efficacy of PD-1 inhibitors through immune and metabolic mechanisms. In this article, we summarize the reported negative impact of sarcopenia on the effectiveness of PD-1 inhibitors in the treatment of NSCLC in recent years. Based on existing research results, we analyze the possible mechanisms by which sarcopenia affects the efficacy of PD-1 inhibitors and discuss possible strategies to address this issue. This could help to understand the impact of sarcopenia on the treatment of PD-1 inhibitors and provide more accurate expectations of treatment outcomes for clinicians and patients. Additionally, we present tailored intervention strategies for sarcopenic patients undergoing PD-1 inhibitor therapy, aiming to optimize treatment efficacy and enhance patient quality of life. Nevertheless, further research is warranted to elucidate the mechanisms through which sarcopenia impacts PD-1 inhibitors and to identify more efficacious intervention approaches for improving the effectiveness of PD-1 inhibitor treatment in sarcopenic patients.